A 6‐month observational study of changes in objectively measured physical activity during weight loss in dogs. (29th October 2014) - Morrison, R.; Reilly, J. J.; Penpraze, V.; Pendlebury, E.; Yam, P. S.
<x xml:space="preserve">Abstract</x> OBJECTIVES To evaluate long‐term changes in physical activity and sedentary behaviour during weight loss in dogs. METHODS Sixteen overweight and obese dogs undergoing a 6‐month calorie‐controlled weight‐loss programme wore Actigraph GT3X accelerometers (Actigraph, FL) for three consecutive days each month for the duration of the programme. Total volume of physical activity and time spent in sedentary behaviour, light‐moderate intensity physical activity and vigorous intensity physical activity were extracted from the accelerometer data and compared from baseline to month 6. RESULTS Valid accelerometry data were returned for 14 of 16 dogs. Mean percentage weight loss over 6 months was 15% of initial bodyweight. There was no marked increase in any of the physical activity outcomes or reduction in sedentary behaviour. CLINICAL SIGNIFICANCE Substantial weight loss was not associated with a spontaneous increase in physical activity or reduction in sedentary behaviour. Although the dogs in this study lost a substantial amount of bodyweight without a measured increase in physical activity, dog owners should still be encouraged to facilitate increased physical activity in their dogs owing to the wide range of benefits associated with physical activity other than weight loss.